2014
DOI: 10.1186/1756-8935-7-5
|View full text |Cite
|
Sign up to set email alerts
|

The PEG13-DMR and brain-specific enhancers dictate imprinted expression within the 8q24 intellectual disability risk locus

Abstract: BackgroundGenomic imprinting is the epigenetic marking of genes that results in parent-of-origin monoallelic expression. Most imprinted domains are associated with differentially DNA methylated regions (DMRs) that originate in the gametes, and are maintained in somatic tissues after fertilization. This allelic methylation profile is associated with a plethora of histone tail modifications that orchestrates higher order chromatin interactions. The mouse chromosome 15 imprinted cluster contains multiple brain-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 40 publications
5
55
0
Order By: Relevance
“…Therefore, it seems reasonable to posit that mutations in TrappC9 may alter its ability to function in this signaling pathway. Indeed, several recent studies further implicated TrappC9 in the NF-κB pathway and in neuronal differentiation (71,72) and, although widely expressed, TRAPPC9 expression appears highest in the cerebellum consistent with the notion that it may have a brain-specific function outside of its role in TRAPP II (73). If this protein functions in both membrane traffic and the NF-κB pathway, then TrappC9 may be viewed as a so-called 'moonlighting' protein (74).…”
Section: Intellectual Disability In Individuals With Trappc9 Mutationmentioning
confidence: 61%
“…Therefore, it seems reasonable to posit that mutations in TrappC9 may alter its ability to function in this signaling pathway. Indeed, several recent studies further implicated TrappC9 in the NF-κB pathway and in neuronal differentiation (71,72) and, although widely expressed, TRAPPC9 expression appears highest in the cerebellum consistent with the notion that it may have a brain-specific function outside of its role in TRAPP II (73). If this protein functions in both membrane traffic and the NF-κB pathway, then TrappC9 may be viewed as a so-called 'moonlighting' protein (74).…”
Section: Intellectual Disability In Individuals With Trappc9 Mutationmentioning
confidence: 61%
“…This protein has been implicated in neural differentiation,15 and inactivation in PC12 cells prevents nerve growth factor-induced neurite outgrowth 14. Its expression is highest in the human cerebellum, suggesting that TrappC9 may have a brain-specific signalling function outside of its general role in membrane trafficking 16. Several children with intellectual disability and microcephaly have been found to carry mutations in TRAPPC9 8–11 17.…”
Section: Discussionmentioning
confidence: 99%
“…Imprinted lncRNAs range in length from ϳ1.6 kb to ϳ1000 kb, and thus, many imprinted lncRNAs are also classified as macro lncRNAs due to their extraordinary length (Guenzl and Barlow 2012). To date, seven imprinted lncRNAs have been identified that are regulated by imprinted gDMRs and are conserved between mice and humans: Airn, Gtl2, H19, Kcnq1ot1, Nespas, Peg13, and Ube3a-as (Brannan et al 1990;Gray et al 1999;Smilinich et al 1999;Lyle et al 2000;Paulsen et al 2001;Coombes et al 2003;Court et al 2014). Similar to Xist, these lncRNAs are thought to have a role in mediating long-range control of imprinted gene transcription.…”
Section: Genomic Imprintingmentioning
confidence: 99%